A Budget Impact Model for Paclitaxel-eluting Stent in Femoropopliteal Disease in France - De Cock, Erwin (Springer-Verlag, 2012)
PURPOSE: The Zilver PTX drug-eluting stent (Cook Ireland Ltd., Limerick, Ireland) represents an advance in endovascular treatments for atherosclerotic superficial femoral artery (SFA) disease. Clinical data demonstrate improved clinical outcomes compared to bare-metal stents (BMS). This analysis assessed the likely impact on the French public health care budget of introducing reimbursement for the Zilver PTX stent. METHODS: A model was developed in Microsoft Excel to estimate the impact of a progressive transition from BMS to Zilver PTX over a 5-year horizon. The number of patients undergoing SFA stenting was estimated on the basis of hospital episode data. The analysis from the payer perspective used French reimbursement tariffs. Target lesion revascularization (TLR) after primary stent placement was the primary outcome. TLR rates were based on 2-year data from the Zilver PTX single-arm study (6 and 9 %) and BMS rates reported in the literature (average 16 and 22 %) and extrapolated to 5 years. Net budget impact was expressed as the difference in total costs (primary stenting and reinterventions) for a scenario where BMS is progressively replaced by Zilver PTX compared to a scenario of BMS only. RESULTS: The model estimated a net cumulative 5-year budget reduction of €6,807,202 for a projected population of 82,316 patients (21,361 receiving Zilver PTX). Base case results were confirmed in sensitivity analyses. CONCLUSION: Adoption of Zilver PTX could lead to important savings for the French public health care payer. Despite higher initial reimbursement for the Zilver PTX stent, fewer expected SFA reinterventions after the primary stenting procedure result in net savings.